2015
DOI: 10.1039/c5ra08469e
|View full text |Cite
|
Sign up to set email alerts
|

Fast and clean functionalization of MWCNTs by DBD plasma and its influence on mechanical properties of C–epoxy composites

Abstract: Multiwalled carbon nanotubes (MWCNTs) were functionalized under helium/air plasma and the surface characteristics were compared with that of chemical functionalization. Changes in surface functional groups of MWCNTs due to plasma/chemical treatment were estimated by using temperature programmed decomposition (TPD), elemental analysis, Raman spectroscopy and BET surface area analysis. Raman spectroscopic studies highlighted that chemical functionalization increases the degree of disorder for MWCNTs when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[ 22,23 ] Plasma functionalization has several advantages over wet chemical functionalization, including shorter treatment times, reduced damage to the CNT structure and reduced environmental impact as no wastewater is produced. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22,23 ] Plasma functionalization has several advantages over wet chemical functionalization, including shorter treatment times, reduced damage to the CNT structure and reduced environmental impact as no wastewater is produced. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Plasma functionalization has several advantages over wet chemical functionalization, including shorter treatment times, reduced damage to the CNT structure and reduced environmental impact as no wastewater is produced. [24,25] Many studies have been conducted to optimize the conditions (e.g., applied power, process pressure, and gas type) for plasma functionalization. [26][27][28] However, achieving functionalization in the deepest regions of CNTs within a suitable treatment time for industrial applications has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…So far, different CVD strategies, such as initiated CVD (iCVD) and plasma‐enhanced CVD (PECVD), have been employed to modify CNT surfaces. Previously, it was reported that PECVD‐modified CNTs show better interface compatibility with an epoxy matrix, compared to those with chemical functionalization . In another study, CNTs were modified by PECVD to improve their dispersion capability in water …”
Section: Introductionmentioning
confidence: 99%
“…matrix, compared to those with chemical functionalization. 22 In another study, CNTs were modified by PECVD to improve their dispersion capability in water. 23 In this study, CNTs were encapsulated with poly(hexafluorobutyl acrylate) (PHFBA) thin films by PECVD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with bare electrode discharge, the electrodes of dielectric barrier discharge (DBD) are covered or separated by dielectrics, therefore resulting in their different characteristics. During the past decade, atmospheric pressure DBD plasma treatment of polymers and silicon has been widely studied [9,[21][22][23][24][25][26], while that of metal substrates still requires further research. Bónová et al [27] reported that APPJ generated by DBD could hydrophilise flat aluminium surfaces within 1 s, which is much more efficient than APPJ generated by bare electrode discharge.…”
mentioning
confidence: 99%